Diffuse scattering and physical optics in the propagation of electromagnetic waves applied to mobile communications (2021)
In this work, the optical theory of physics helps to understand, analyze, and calculate the received power in a fifth-generation mobile telecommunications receiver. In these communication systems there are statistical models and deterministic physical models. We investigated how diffuse scattering in reflection contributes to specular reflection in received power at a receiver due to materials in the propagating environment in a communication channel using millimeter waves. The dimensions of building construction materials have sizes comparable to wavelength at millimeter wave frequencies. The power transmitted by communication equipment can be reflected in the roughness of these apparently smooth materials or spread out in multiple directions. The results show that the contribution due to diffuse scattering must be considered and that deterministic physical models using optical theory are valid and improve predictive analysis with good fit. With these results, the physical theory allows to make software with high precision and that improves the current applications.